THE ROLE OF INTERNATIONAL FINANCIAL INSTITUTIONS IN STABILIZING GLOBAL MARKET (E Global Congress, 2025)
International Financial Institutions (IFIs) such as the International Monetary Fund (IMF), World Bank, and regional development banks play a pivotal role in promoting global economic stability and growth. This article explores the mechanisms through which these institutions stabilize global markets, including financial assistance programs, monetary surveillance, technical support, and policy advice. It also examines the challenges IFIs face in addressing global crises such as financial downturns, pandemics, and geopolitical tensions. The paper highlights real-world examples of IFI interventions and evaluates their effectiveness in reducing systemic risk, fostering resilience, and supporting sustainable development in vulnerable economies. Finally, it discusses the need for reforms in global financial governance to enhance transparency, inclusiveness, and responsiveness in an increasingly interconnected world.